2018
DOI: 10.1515/opag-2018-0022
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oil cakes and garlic aqueousbased formulations of trichoderma viride on management of meloidogyne incognita in chilli

Abstract: Root-knot nematode, Meloidogyne incognita (Kofoid and White) is a major threat to chilli (Capsicum annum) cultivation, by forming root galls and subsequent wilting. These nematodes live in soil, roots debris and reported surviving in other Solanaceae crops. Chemical application of nematicides cause impact on environment, therefore biocontrol using antagonistic fungi is desired to tackle this problem. This research is aimed to evaluate the effect of Trichoderma viride and its formulations on management of M. in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Pervez et al (2017) reported that T. harzianum growth was inhibited differently by different concentration of plant extracts, and maximum inhibition percentage of 50.2 and 52.3 at 5% and 10% concentration of Lantana (Lantana camara). Nirosha et al (2018) stated further that Mahua oil cake extract caused the least mycelial growth in T. viridae. But there is no any study related to the antifungal effect of Tea and coffee on Trichoderma spp.…”
Section: Resultsmentioning
confidence: 99%
“…Pervez et al (2017) reported that T. harzianum growth was inhibited differently by different concentration of plant extracts, and maximum inhibition percentage of 50.2 and 52.3 at 5% and 10% concentration of Lantana (Lantana camara). Nirosha et al (2018) stated further that Mahua oil cake extract caused the least mycelial growth in T. viridae. But there is no any study related to the antifungal effect of Tea and coffee on Trichoderma spp.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies reported that oil cake applications reduced the Meloidogyne spp. population and thereby increasing plant growth and yield of different crops (Yadav et al, 2005;Nirosha et al, 2018).…”
mentioning
confidence: 99%